Impacto dos serviços farmacêuticos na saúde da população de Parnamirim/RN: percepção dos farmacêuticos - Farias, Laryssa Freire Medeiros de (2022)
This study aimed to evaluate the perception of pharmacists in charge of technicians (R.T.) who work in drugstores in Parnamirim/RN, about the importance of pharmaceutical services and their impact on the health of the population. This is a descriptive and exploratory study, with a quantitative approach, in which an online questionnaire was used as a research instrument. The present study took place from October to December 2021. As for the results obtained, the following assertions were obtained: in relation to gender, female the pharmacist technical responsible prevailed (72.5%) and only 27.5% of males, within from an age group between 29 and 38 years old (52.5%); 55% had specialization and the majority (58.8%) were Technical Director, 10% Technical Assistants, 4.9% substitutes and 26.3% owners, these accumulated the functions of owner and Technical Responsible, like many of the 58.8% of the Technical Directors stated that they also accumulated the function of managers. Most drugstores (60%) have already adhered to some pharmaceutical services, although 40% still remain without recognize this practice, and among the services offered, the following were cited: blood pressure measurement (55%), capillary blood glucose (41.3%) and body temperature (31.3%), dispensing (100%), pharmaceutical care (88.8%), placing earrings (40%), pharmacotherapeutic monitoring (41.3%), Covid-19 tests (5%) remote laboratory (5%). All drugstores claimed to carry out the dispensing, which contrasts with the affirmation in which 40% said they did not recognize themselves offering pharmaceutical services. It is also contradictory that 89% of the interviewees claimed to perform pharmaceutical care, without, however, covering the measurement of physiological and biochemical parameters, beyond monitoring of therapy, or administration of injectables. About pharmacists’ opinion, the public that most sought pharmaceutical services, it was women, over 22 years old (62.5%) and the elderly (over 60 years old), making up a total of 85% of these two segments. The vast majority (97.5%) of the interviewees recognize that pharmaceutical services improvement in the clinical condition and quality of life, in addition to promoting adherence and the safety of those who sought pharmaceutical services; 57% of respondents considered themselves safe in the feasibility of pharmaceutical services and, equally prepared by the institution that formed them. Regarding the professional satisfaction that pharmaceutical services bring, 93.8% consider themselves satisfied, in addition, they consider the drugstore a health establishment and pharmacists the care professionals in this environment. In conclusion, it appears that pharmaceutical services are the materialization of pharmaceutical care, and that the feasibility of the services raised self-esteem and the desire to interact more with the community. As for the population, the interviewees point to perceive more security and confidence after the provision of services.